2017
DOI: 10.1158/1078-0432.ccr-16-1469
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker and Tumor Responses of Oral Cavity Squamous Cell Carcinoma to Trametinib: A Phase II Neoadjuvant Window-of-Opportunity Clinical Trial

Abstract: Purpose Ras/MEK/ERK pathway activation is common in oral cavity squamous cell carcinoma (OCSCC). We performed a neoadjuvant (pre-operative) trial to determine biomarker and tumor response of OCSCC to MEK inhibition with trametinib. Patients and Methods Patients with Stage II–IV OCSCC received trametinib (2 mg/day, minimum 7 days) prior to surgery. Primary tumor specimens were obtained before and after trametinib to evaluate immunohistochemistry staining for p-ERK1/2 and CD44, the primary endpoint. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…In 2013, we initiated a PDX study for OCSCC across 114 patients from three cohorts: treatment-naive primary OCSCC patients undergoing standard-of-care primary resection (n = 84), patients enrolled in a neoadjuvant trametinib clinical trial ( ClinicalTrials.gov : NCT01553851; n = 20) ( Uppaluri et al, 2017 ), and patients enrolled in a neoadjuvant pembrolizumab clinical trial ( ClinicalTrials.gov : NCT02296684; n = 10, data not published). PDXs were attempted from treatment-naive tumor samples from all patients (n = 114), post-treatment surgical resections from patients enrolled in the trametinib clinical trial (n = 20) or the pembrolizumab clinical trial (n = 10), and patients with relapsed disease (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, we initiated a PDX study for OCSCC across 114 patients from three cohorts: treatment-naive primary OCSCC patients undergoing standard-of-care primary resection (n = 84), patients enrolled in a neoadjuvant trametinib clinical trial ( ClinicalTrials.gov : NCT01553851; n = 20) ( Uppaluri et al, 2017 ), and patients enrolled in a neoadjuvant pembrolizumab clinical trial ( ClinicalTrials.gov : NCT02296684; n = 10, data not published). PDXs were attempted from treatment-naive tumor samples from all patients (n = 114), post-treatment surgical resections from patients enrolled in the trametinib clinical trial (n = 20) or the pembrolizumab clinical trial (n = 10), and patients with relapsed disease (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Uppaluri et al [103] performed a clinical trial to determine the tumor response of oral cavity squamous cell carcinoma to treatment with the MEK inhibitor trametinib and found that trametinib caused a significant reduction of RAS/MEK/ERK signaling pathway activation and clinical tumor response.…”
Section: Therapeutic Targets For Tumor-intrinsic Signaling In Cancermentioning
confidence: 99%
“…However, convergence of these signals and activation of the MEK and ERK effectors of the MAPK pathway is prevalent and has been targeted in preclinical and early clinical studies. Biomarker and clinical responses to MEK inhibitor Trametinib were recently reported in HNSCC in a window of opportunity trial . MEK inhibitor PD‐0325901 has shown single‐agent activity and ability to overcome resistance and enhance antitumor effects in vivo with the dual PI3K/mTOR inhibitor PF‐384 .…”
Section: Resultsmentioning
confidence: 99%